Occurrence of mycorrhizal spores and phosphate solubilizing potential of rhizosphere mycoflora of seagrass Thalassia hemprechii (Ehrenb.) Asch. - Arumugam Radjasegarin; T Suganya; E Pazhani; N Azhagusundari; G Jayanthi; G Amalan Rabert; V Santhi (Natural Resources for Human Health, 2026)
Phosphorus is one among the chief macronutrients that take part in the various biological processes of plants, and it cannot be replaced by other elements. We examined the arbuscular mycorrhizal fungi (AMF) colonization and phosphate solubilizing potential of fungi from seagrass T. hemprichii (Ehrenb.) Asch., which belongs to the family Hydrocharitaceae collected from the Gulf of Mannar, India. For the first time, we reported the occurrence of AMF spores and phosphate-solubilizing potential of fungal species from the seagrass rhizosphere soil. A total of six mineral phosphates solubilizing fungi were isolated from rhizosphere of seagrass Thalassia hemprichii—five of them belong to the genus Aspergillus and one is from Fusarium. The concentration of soluble-P in the fluid medium ranged between 12.93±0.39 and 42.69±0.22 μg P ml–1, with the lowest by Aspergillus japonicas and the highest by Aspergillus niger. The AMF spores isolated from the rhizosphere belong to genus Glomus, whereas no colonization was found in the roots.